2012
DOI: 10.1002/nml.21040
|View full text |Cite
|
Sign up to set email alerts
|

The nonprofit board as a team: Pilot results and initial insights

Abstract: There is a growing desire for boards of nonprofits to deliver better governance to the organizations they control. Consequently, self‐evaluation has become an important tool for nonprofit boards to meet these expectations and demonstrate that they are discharging their responsibilities effectively. This article describes initial results aimed at developing a psychometrically sound, survey‐based board evaluation instrument based on the Team Development Survey, which assesses the team attributes of an organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…We have two reasons to closely stick to this literature. On a positive note, Nicholson, Newton, and McGregor‐Lowndes () found that the conceptualization of boards as teams holds a great deal of promise for nonprofit governance research. A more critical reading of the literature, however, suggests that it is time the behavioral process–oriented study of boards delivers on its promise of insight in the black box of board dynamics.…”
Section: What Determines Board Performance?mentioning
confidence: 99%
“…We have two reasons to closely stick to this literature. On a positive note, Nicholson, Newton, and McGregor‐Lowndes () found that the conceptualization of boards as teams holds a great deal of promise for nonprofit governance research. A more critical reading of the literature, however, suggests that it is time the behavioral process–oriented study of boards delivers on its promise of insight in the black box of board dynamics.…”
Section: What Determines Board Performance?mentioning
confidence: 99%
“…Moreover, the focus here is on overall board performance, with the assumption that high-performing boards lead to high-performing organizations. Admittedly, additional performance data, e.g., outcome and impact data, financial information, and stakeholder satisfaction measures, would be needed in order to test this assumption (Nicholson, Newton, & McGregor-Lowndes, 2012;Theodos & Firschein, 2016;Voss & Zannie, 2000). Also, as noted in the literature review, there may be other reasons a board would choose to undergo self-assessment, which arguably would generate alternative assumptions guided by different theoretical perspectives (e.g., change management, organizational learning, or institutional crisis).…”
Section: Limitationsmentioning
confidence: 99%
“…It also raises questions about the checks and balances needed to prevent unethical practices. Nicholson, Newton and McGregor-Lowndes (2012) have demonstrated the positive relationship between NPO board performance and NPO effectiveness and Bright (2001) explains that board performance creates a framework for the success or failure of an organisation. The findings suggest that no formal performance evaluations exist for shelter boards/committees.…”
Section: 2mentioning
confidence: 99%